Reforma al art. 386 del código orgánico integral penal, buscando evitar la constante vulneración de los derechos del conductor, en cuanto a las sanciones por contravenciones de tránsito de primera clase - Gordon Portugal, Fani Margoth (2018)
The present work of legal research, I undertake in order to present a legal proposal to be reformed Art. 386 of the Penal Code of Integral concerning sanctioning with three penalties to a misdemeanor, with imprisonment of three days fine of a unified basic wage of workers in general and reduction of ten points on your driver's license, violating the rights of the driver by applying this rule, since the three penalties for a contravention too. This legal research is divided into six chapters. In the first chapter.- the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in the implementation of the research hypothesis. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter, the methodology used in the research described in question; the methods used the types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained through interviews with competent authorities based in the canton Tena, in addition to surveys of lawyers in professional free exercise, you know as they are violated without any consideration rights driver not punished him with one penalty but three times violating the rights of it. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter speaks of the Proposal, Objectives, Proposal description of the Beneficiaries and Social Impact, etc.